Urban Regeneration Strategies for Enhancing Livability: A Case Study of the Chaktai Commercial Area, Chattogram, Bangladesh - Sarah Binte Haque; Moumita Roy; Zereen Afroz Tanha (Alanya Üniversitesi, 2024)
Bangladesh has been experiencing rapid urbanization and economic growth, motivating people to move towards the cities. Consequently, commercial areas of the cities are becoming highly occupied. The issue of overpopulation leads to congestion and shortage of open spaces, both reserved and publicly accessible, in such areas of the cities, affecting the physical and mental health of the users of these areas. To understand this situation, Chattogram in particular, the Chaktai commercial area is identified as the case study area for further investigation and research. This study will examine the present scenario of this densely built commercial area through an empirical analysis and field survey, focusing on collecting data related to major land-use types, street characteristics, major activities, traffic analysis, and environmental conditions. Additionally, an observational approach will be employed, along with one-to-one interviews and Focus Group Discussions (FGD), to gather user feedback on the space. By examining urban regeneration strategies for Asadganj, this study offers guidelines to improve conditions for its users including residents, business holders, and workers, to enhance the area's quality of life.